Remote Effects of IOD and ENSO on Motivating the Atmospheric Pattern Favorable for Snowfall Over the Tibetan Plateau in Early Winter - Shen, Hongyan; Gong, Zhiqiang; Liu, Boqi; Guo, Yipeng; Feng, Xiaoli; Wen, Tingting; Wang, Xiaojuan; Feng, Guolin (Frontiers in Climate, 2021)
Interannual variation of snowfall over the Tibetan Plateau (TP) in early winter (November-December) and its related atmospheric attribution are clarified. Meanwhile, the influence of tropical sea surface temperatures (SSTs) on TP snowfall is investigated by diagnostic analysis and Community Atmosphere Model (CAM5) simulations.